Features of adolescents time perception in the context of their living activity - Pogoril'ska, N.; Matsionova, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article defines the connection between the individual peculiarities of time perception and the levels of personal life activity. The results of the empirical study suggest that the diversity of levels in the perception of time in the adolescent psyche depends on a number of factors, including innate biological cycles t, ending with a complex subjective sense of time (in the context of age-related changes). Accordingly, it eliminates the contradiction between the uncertainties of the opposing time of the subject. Theoretical analysis of the factors that determine the perception of a teenager’s personality provides an opportunity to make a prediction in social and psychological development in the context of accelerated social life. From the considered theories of understanding of time, the most comprehensive concept in the context of adolescent life activity is the definition of time as a directed value (vector), the unambiguous definition of which implies not only a system of units of measure (second, minute, hour, day, month, year, century), but and the constant starting point from which the account is maintained. The article made a comparative analysis of hysterical traits of the subjects with middle and high activity level of life, as well as the analysis of memories of adolescents with medium and high level of life activity. On the basis of the empirical research the features of time orientation of adolescence personality are revealed and factors that influence the formation of time measurement accuracy. The domestic and foreign theoretical approaches, empirical researches of concepts of the time orientation of the personality and vital activity in particular are analyzed. On the basis of the empirical research, features of the age orientation of the adolescent age and factors influencing the formation of the accuracy of time measurement are revealed.